Handbook of Global Logistics Transportation in International Supply Chains - Bookbinder, James H.; SpringerLink (Online service) (New York, NY : Springer New York : Imprint: Springer, 2013)
Global logistics entails tradeoffs in facility location, distribution networks, the routing and scheduling of deliveries by different modes of travel (e.g., air, water, truck, rail), procurement, and the overall management of international supply chains. In an increasingly global economy, then, logistics has become a very important matter in the success or failure of an organization. It is an integral part of supply chain management that involves not just operations management considerations, but production engineering and regional science issues as well. As Director of the prestigious Waterloo Management of Integrated Manufacturing Systems Research Group (WATMIMS), which specializes in logistics and manufacturing, Jim Bookbinder is uniquely qualified to edit a handbook on global logistics. He has aligned a set of prominent contributors for this volume. The chapters in the Handbook are organized into discrete sections that examine modes; logistics in particular countries; operations within a free-trade zone; innovative features impacting international logistics; case studies of specific companies; and a look toward the future. Contributors are from the Americas, Europe, and Asia, and they push the state of the art in areas such as trade vs. security; border issues; cabotage within NAFTA; Green logistics corridors within the EU; inland ports; direct-to-store considerations; and all the questions that need to be confronted in any given region. This will certainly appeal to researchers and practitioners alike, and could serve as required or supplementary reading in graduate-level logistics courses as well.
Logistics in China -- Electronic Procurement Systems in India: Importance and Impact on Supply Chain Operations -- Use of Third Party Logistics Services: An Asia-Pacific Perspective -- The Greater Mekong Sub-region of Southeast Asia: Improving Logistics Connectivity -- Strategic and Tactical Modeling in the Argentine Sugar Industry -- Integration of International and Cabotage Container Shipping in Brazil -- Latin American Logistics/Supply Chain Management: Perspective from the Research Literature -- Logistics in the Oresund Region of Scandinavia -- Green Corridors in European Surface Freight Logistics -- Containerized Freight Distribution in North America and Europe -- Network Redesign in Turkey: The Supply, Production, and Distribution of Malt and Beer -- Procurement from Developing Countries -- Innovative Logistics in Extreme Conditions: The Case of Health-Care Delivery in Gambia -- Comparative Analysis of Air Freight Networks in Regional Markets Around the Globe -- Business Models and Network Design in Hinterland Transport -- Cross-Border Issues and Research -- On the Relationships Among Facility Location, Transportation Mode Selection and Material Flow Costs in Global Supply Chains. Humanitarian Logistics: Advanced Purchasing and Pre-positioning of Relief Items -- Logistics-Intensive Clusters: Global Competitiveness and Regional Growth -- Proactive Order Consolidation in Global Sourcing -- The Future.
Keywords: Economics; Operations research; Economics/Management Science; Operation Research/Decision Theory